A novel method for the determination of the change in blade tip timing probe sensing position due to steady movements. (1st July 2019) - Mohamed, Mohamed; Bonello, Philip; Russhard, Peter
Highlights: A novel method for quantifying steady movement from BTT data is presented. The movement types considered are axial shift, blade lean, and blade untwist. Actual sensing positions of the probes relative to the blades can be determined. The method depends only on the probe data and the chord stagger angle. The change in BTT displacement average is monitored along a range of speed. Abstract: The correlation of blade tip timing (BTT) measurements against strain gauge (SG) measurements and finite element (FE) predictions includes a number of uncertainties. One of the main ones is the steady movement of the blades (i.e. change in their mean position and orientation). This causes the sensing positions of the probes relative to a blade tip to deviate from their intended (nominal) positions, leading to deceptive results for the BTT amplitude and the corresponding stress levels. Such movements are caused by variations in static loading conditions (thermal and pressure) associated with changes in the operating speed. A novel method is introduced for the determination of three basic types of blade tip steady movements: axial; lean; untwist. The method relies on linking the shift in the averages of the BTT data to a number of geometrical relations, depending on the type of movement. Not more than two probes (to be placed at different axial positions) are needed to measure all three types of movement. The method is validated by simulations using a novel BTT simulator, and by measurements from both a test rig and real engine tests. The validated results demonstrate the great potential of the method for practical applications.